Quality of Life of Elderly Patients Undergoing Hemodialysis Therapy in a Hemodialysis Unit - Meilita Enggune; Andro Ruben Runtu; Ever Mario Lontaan; Amelia Adelina Kawulusan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Patients undergoing hemodialysis therapy who have poor quality of life tend to have higher mortality rates compared to the normal population. Quality of life can be an important measure in evaluating the effectiveness of hemodialysis; therefore, improving quality of life is a significant goal in managing patients with Chronic Kidney Disease. Generally, the quality of life of the elderly declines due to decreased physical and psychological abilities. This study aims to assess the quality of life of elderly patients undergoing hemodialysis therapy at the Hemodialysis Unit of GMIM Bethesda Hospital in Tomohon. A quantitative descriptive research method was employed with 20 respondents. The results indicate that 18 respondents (90%) reported good quality of life, while 2 respondents (10%) reported moderate quality of life. It is recommended that nurses in the Hemodialysis Unit provide increased support, especially for elderly patients, to enhance their quality of life during therapy.